A necessary change from 'man' to 'hommo sapiens' : an ecocritical study of Oryx and crake and The year of the flood by Margaret Atwood - Faure, Elizabeth (2015)
It is undeniable that the deteriorating situation of the ecosystem is one of the hottest issues in our world today and indeed one worth contemplating in literary productions. Questions like the destruction of the forests, the extinction of species and the pollution of the air, water and soil have been increasingly attracting writers‟ attention. Ecocritical theories have developed as a consequence of the intervention and subsequent devastation that man is causing to the environment. In The Ecocriticism Reader (1996), Glotfelty defines ecocriticism as the study of “the relationship between literature and the physical environment”, of the way ideas about nature and man‟s interrelation with the natural world are depicted in literary texts (xviii). In the introduction to Ecocritical Explorations in Literary and Cultural Studies (2009), Murphy asserts that literature is a “manifestation and shaping force of human experimental behaviour” (2). For that reason, it is essential for ecocritics to discern how man‟s attitudes towards other living creatures and the status of humankind within the ecosystem are represented in literary texts.